Equine Genomics. - Chowdhary, Bhanu P. (Wiley, 2013)
Analysis of the equine genome began just over a decade ago, culminating in the recent complete sequencing of the horse genome. The availability of the equine whole genome sequence represents the successful completion of an important era of equine genome analysis, and the beginning of a new era where the sequence information will catalyze the development of new tools and resources that will permit study of a range of traits that are economically important and are significant to equine health and welfare. Equine Genomics provides a timely comprehensive overview of equine genomic res.